Plan de bienestar social y satisfacción laboral de los colaboradores de división campo-Casa Grande de la Empresa Casa Grande 2022 - Peláez Chávez, Ana Lucía (2023)
The research presented was carried out with the purpose of analyzing the influence of the Social Welfare Plan on the job satisfaction of employees of the Campo-Casa Grande division of the Casa Grande Company in 2022, with a sample of 156 employees. In the research process, the inductive - deductive, analytical – synthetic methodology and the statistical method were used, for which observation and the survey were used as techniques that were visualized through the observation record and the interview questionnaire to be able to measure the variables of all members of the population. According to the results, it was evidenced that the wellness plan positively influences the degree of job satisfaction of the employees, which shows that only 5.13% do not feel a link of belonging to the company. Likewise, 57.05% of the collaborators have a high feeling of productivity within their work and it makes them feel high levels of job satisfaction.